Ceftriaxone Suppresses Group II Metabotropic Glutamate Receptor Expression Contributing to Reversal of Recognition Memory Deficits of Amyloid Precursor Protein/Presenilin 1 AD Mice - Fan, ShuJuan; Li, Li; Liu, LiRong; Li, He; Xian, XiaoHui; Li, WenBin (Frontiers in Neuroscience, 2022)
Group II metabotropic glutamate receptors (Group II mGluRs) are the peri-synaptic receptor of glutamatergic neurons and negatively regulate glutamate release from presynaptic neurons. Glutamate in the synaptic cleft is mainly taken into astrocytes by glutamate transporter-1 (GLT-1), which primarily expresses in astrocytes. Increasing evidence showed that inhibiting or suppressing the activation of Group II mGluRs would contribute to the improvement of learning and memory deficits in AD animal models. Ceftriaxone (Cef) has been reported to alleviate spatial memory deficits in AD model mice by improving GLT-1-related clearance and metabolism of glutamate. Therefore, the present study further investigates the improving effect of Cef on recognition memory deficits and the involvement of Group II mGluRs in the process using the APP/PS1 AD mouse model. Novel object recognition tests showed that Cef treatment significantly improved the recognition memory deficits of the AD mice. Western-blot and immunohistochemistry analysis showed that Cef treatment significantly suppressed the upregulation of Group II mGluRs expression in APP/PS1 AD mice. The above suppression effect of Cef was blocked by dihydrokainic acid, an inhibitor of GLT-1 uptake activity. Furthermore, the Cef treatment significantly restored the downregulation in the downstream molecules of Group II mGluRs activation including the expression of PKA and phosphorylated SNAP-25 in the APP/PS1 AD mice. The Cef treatment had no effect on the content of Aβ40 and Aβ42 in the hippocampus of APP/PS1 AD mice. The above results suggested that suppression of Group II mGluRs contributed to the Cef-induced improvement on the recognition memory deficits in APP/PS1 AD mice.